Die Angst zum Laufen bringen – Herta Müllers Text-Bild-Collagen und ihre polnischen Übersetzungen - Sommerfeld, Beate (Studia Germanica Posnaniensia, 2014)
Herta Müller, born in Rumania as a member of the German minority, began to create her collages after having immigrated to West Germany. Being heterogeneous combinations of words and pictorial ele-ments cut out from print media, the collages can be considered as an attempt to forge a link between west German culture and life in Rumania under the dictatorship of Ceauşescu. An important role in the articulation of autobiographical experience plays a specific rhythm, which is characterized by intermo-dality and criss-crossed words and pictorial elements. Rhythm not only renders experience – as to speak subcutaneously – apt to be communicated, deliberate ruptures of rhythm indicate the traumatizing ef-fects of past experiences and anxiety. The article analyses to what extent the polish translators Leszek Szaruga and Andrzej Kopacki take into account the structural complexity and intermediality of the collages.